Synthesis, Characterization and In Vitro Antibacterial Studies of Organotin(IV) Complexes with 2-Hydroxyacetophenone-2-methylphenylthiosemicarbazone (H2dampt) - M. A. Salam; M. A. Affan; Ramkrishna Saha; Fasihuddin B. Ahmad; Norrihan Sam (Bioinorganic Chemistry and Applications)
Five new organotin(IV) complexes of 2-hydroxyacetophenone-2-methylphenylthiosemicarbazone [H2dampt, (1)] with formula [RSnCl𝑛−1(dampt)] (where R=Me, 𝑛=2 (2); R=Bu, 𝑛=2 (3); R=Ph, 𝑛=2 (4); R=Me2, 𝑛=1 (5); R=Ph2, 𝑛=1 (6)) have been synthesized by direct reaction of H2dampt (1) with organotin(IV) chloride(s) in absolute methanol. The ligand (1) and its organotin(IV) complexes (2–6) were characterized by CHN analyses, molar conductivity, UV-Vis, FT-IR, 1H, 13C, and 119Sn NMR spectral studies. H2dampt (1) is newly synthesized and has been structurally characterized by X-ray crystallography. Spectroscopic data suggested that H2dampt (1) is coordinated to the tin(IV) atom through the thiolate-S, azomethine-N, and phenoxide-O atoms; the coordination number of tin is five. The in vitro antibacterial activity has been evaluated against Staphylococcus aureus, Enterobacter aerogenes, Escherichia coli, and Salmonella typhi. The screening results have shown that the organotin(IV) complexes (2–6) have better antibacterial activities and have potential as drugs. Furthermore, it has been shown that diphenyltin(IV) derivative (6) exhibits significantly better activity than the other organotin(IV) derivatives (2–5).